2011
DOI: 10.1177/0954406211429410
|View full text |Cite
|
Sign up to set email alerts
|

Dry tribology and nanomechanics of gaseous flame soot in comparison with carbon black and diesel soot

Abstract: Ethylene gas is burnt and the carbon soot particles are thermophoretically collected using a home-built equipment where the fuel air injection and intervention into the 7.5-cm long flame are controlled using three small pneumatic cylinders and computer-driven controllers. The physical and mechanical properties and tribological performance of the collected soot are compared with those of carbon black and diesel soot. The crystalline structures of the nanometric particles generated in the flame, as revealed by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The particles have a 7 nm diameter and varying degrees of crosslinking. The particles exhibit elastoplastic behaviour as in previous nanoindentation experiments [39,37,38]. It can be observed that the maximum load and the slope of the curves increases with the degree of crosslinking in the particle.…”
Section: Particles Without Shellsupporting
confidence: 66%
See 1 more Smart Citation
“…The particles have a 7 nm diameter and varying degrees of crosslinking. The particles exhibit elastoplastic behaviour as in previous nanoindentation experiments [39,37,38]. It can be observed that the maximum load and the slope of the curves increases with the degree of crosslinking in the particle.…”
Section: Particles Without Shellsupporting
confidence: 66%
“…Nanocrystalline graphite is a noncrosslinked structure made of mobile graphene sheets, possessing very low hardness values (0.1-0.4 GPa) [36]. In contrast, soot shows hardness values of 2-8 GPa [37,38,39,40], values closer to a hard crosslinked structure such as charcoal (3-5 GPa) [41]. The wide range found for soot hardness suggests that particles collected at different residence times and produced in different combustion environments may be characterised by different structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…The final paper in this special issue on Advanced Materials Engineering is entitled ''Dry tribology and nanomechanics of gaseous flame soot in comparison with carbon black and diesel soot'' [11]. It is from an Indian research group and deals with carbon soot particles that are collected thermophoretically from burning ethylene gas.…”
mentioning
confidence: 99%